2004
DOI: 10.1007/s10096-004-1247-9
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of identification and susceptibility results by direct inoculation of Vitek 2 cards from positive BACTEC cultures

Abstract: Rapid identification of bacteria and prompt acquisition of susceptibility results are valuable for patient care. The objective of the present study was to determine the accuracy of direct inoculation of Vitek 2 cards from positive BACTEC cultures compared to inoculation of the cards from subculture plates. Positive BACTEC cultures sampled between March 2001 and June 2002 were included. The results of direct inoculation were compared with the results of inoculation of Vitek 2 cards from subcultures. Of 161 gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 17 publications
3
18
0
1
Order By: Relevance
“…These errors thus would not have clinical consequences. Funke et al [18] also described a categorical agreement of 99.0%, which is comparable with or higher than results from studies on other direct methods of AST [7,13-16,26]. Therefore, we conclude that also for GNR, results of the direct Phoenix method for AST can be used to guide antibiotic therapy in bloodstream infections.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…These errors thus would not have clinical consequences. Funke et al [18] also described a categorical agreement of 99.0%, which is comparable with or higher than results from studies on other direct methods of AST [7,13-16,26]. Therefore, we conclude that also for GNR, results of the direct Phoenix method for AST can be used to guide antibiotic therapy in bloodstream infections.…”
Section: Discussionsupporting
confidence: 84%
“…Other studies that presented results of direct methods for AST of GPC showed variable results [13-16,25,26], which makes comparison difficult. But our results were comparable to those of the routine Phoenix method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Se eliminó el sobrenadante y se removió el sedimento en la Laboratorio Clínico, Clínica Alemana de Santiago. superficie de gel con una tórula, para resuspenderlo en 2 ml de solución salina 0,45% y ajustarlo a McFarland 0,5-0,63 3 . Las suspensiones obtenidas mediante ambos protocolos fueron cargadas en las tarjetas Vitek 2 AST 249, según instrucciones del fabricante.…”
unclassified